A New Approach to Supramolecular Structure Determination in Pharmaceutical Preparation of Self-Assembling Peptides: A Case Study of Lanreotide Autogel - Manuela Grimaldi; Angelo Santoro; Michela Buonocore; Claudio Crivaro; Nicola Funicello; Matilde Sublimi Saponetti; Cristina Ripoli; Manuela Rodriquez; Salvatore De Pasquale; Fabrizio Bobba; Lucia Ferrazzano; Walter Cabri; et al. (MDPI AG, 2022)
The supramolecular structure in peptides' prolonged-released gel formulations is the most critical parameter for the determination of the pharmaceutical profile of the drug. Here, we report our investigation on lanreotide Autogel as a case study. For the first time, we describe the use of the pulsed field gradient (PFG) diffusion-ordered spectroscopy (DOSY) magic-angle spinning NMR to characterize the supramolecular self-assembly and molecular mobility of different samples of lanreotide Autogel formulations prepared according to different formulation protocols. The diffusion coefficient was used to calculate the hydrodynamic radii of supramolecular assemblies and build relative molecular models. DOSY data were integrated with NMR imaging (MRI) measurements and atomic force microscopy (AFM) imaging.